Promoting creative confrontations - Brna, Paul (1990)
Abstract: "We outline a methodology for confronting students with the inconsistencies entailed by their own beliefs. We illustrate this with reference to one particular physics subdomain which stresses an understanding of process (how things are made to happen): the dynamics domain. The aspects of the methodology described are: the construction of a variety of situations which are expected to cause a student some conceptual difficulty; the predictions made by the student prior to modelling; and the observations of the student's attempts to model the situation. We use a case study to illustrate the approach."
Keywords: Computer software; Education and training; Psychology; Belief; Cognition